1985
DOI: 10.1017/s0003356100036369
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the body composition of cattle exhibiting compensatory growth and the modifying effects of grazing management

Abstract: Friesian steer calves born in August were reared from 3 to 7 months of age on either a low (OL) or high (OH) plane of nutrition. A further group born in October (YH) was also reared on a high plane. At grazing, the performance of calves of the same age but different weights (OL v. OH) or the same weight but different ages (OL v. YH) were compared at two levels of herbage allowance, either 30 or 60 kg dry matter per kg live weight. During the winter, the H groups received silage and concentrate and the L group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
3
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 16 publications
1
14
3
1
Order By: Relevance
“…The phenomenon of animals showing enhanced performance after periods of nutritional restriction has been known for many years and has been comprehensively reviewed (Wilson and Osbourn, 1960;Allden, 1970;O'Donovan, 1984). Several explanations have been proposed as to the cause of this compensation including reduced maintenance requirements (Saubidet and Verde, 1976), alterations of the composition of tissue gains (Thompson, Bickel and Schiirch, 1982;Baker, Young and Laws, 1985) and increased food intake (Meyer, Hull, Weitkamp and Bonilla, 1965). In the present experiments, a reduction in winter food level led to increased herbage intake at pasture and increased live-weight gains.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The phenomenon of animals showing enhanced performance after periods of nutritional restriction has been known for many years and has been comprehensively reviewed (Wilson and Osbourn, 1960;Allden, 1970;O'Donovan, 1984). Several explanations have been proposed as to the cause of this compensation including reduced maintenance requirements (Saubidet and Verde, 1976), alterations of the composition of tissue gains (Thompson, Bickel and Schiirch, 1982;Baker, Young and Laws, 1985) and increased food intake (Meyer, Hull, Weitkamp and Bonilla, 1965). In the present experiments, a reduction in winter food level led to increased herbage intake at pasture and increased live-weight gains.…”
Section: Discussionmentioning
confidence: 45%
“…It is probably that the higher growth rates of cattle exhibiting compensatory growth are only partly due to enhanced intakes since it has been demonstrated that during compensatory growth cattle deposit more protein and water (Baker et al, 1985). When steers that had been restricted were realimenated on the same level of intake in relation to live weight as control steers they still exhibited higher growth rates indicating that the energy concentration of the liveweight gain was lower (Thompson et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact cause of the phenomenon in cattle has been the subject of much debate. Compensatory growth has been associated with reduced maintenance requirements (Saubidet and Verde, 1976;Ledger and Sayers, 1977), increased food intake (Meyer et al, 1965;O'Donovan et al, 1972;Wright et al, 1986Wright et al, , 1987 and changes in the composition of tissue gained (Meyer et al, 1965;Fox et aL, 1972;Baker et al, 1985).…”
Section: Body Condition Scorementioning
confidence: 99%
“…The non-productive animals are subjected to various degrees of undernutrition in different seasons of the year (Chaturvedi et al, 2008) and hence re-alimentation increases gut fill besides some functional or structural changes in internal organs, particularly liver, kidney, heart and digestive tract (Baker et al, 1985). Studies on meat quality also indicate that a high growth rate before slaughter has a positive impact on meat tenderness (Muir et al, 2001).…”
Section: Introductionmentioning
confidence: 99%